Somewhere over the rainbow Discussions on homosexuality in education across Europe - De Witte, Kristof; Holz, Oliver; Geunis, Lotte (Waxmann Verlag, 2018)
Schools should offer a safe and secure environment for all young people to develop, to learn, and to thrive. Sadly, for many, they fall short. Homophobic and transphobic behaviour is still painfully common in schools across Europe. A significant number of LGBT pupils experience homophobic and transphobic bullying, and they are more likely to experience violence than heterosexual peers. This publication explores the underlying attitudes towards homosexuality in eight European countries: Belgium, Germany, Hungary, Poland, Spain, the Netherlands, the United Kingdom and Turkey. It is the product of a strategic partnership (KA2) between fifteen European secondary and higher education institutions, launched in 2016 under the auspices of the European Commisson's ERASMUS+ programme. The project supported by this partnership, Homo'poly, promotes greater understanding and acceptance of homosexuality with the explicit aim of improving the school life of LGB pupils.